Yeast Protein as an Easily Accessible Food Source - Jach, Monika Elżbieta; Serefko, Anna; Ziaja, Maria; Kieliszek, Marek (Metabolites, 2022)
In recent years, the awareness and willingness of consumers to consume healthy food has grown significantly. In order to meet these needs, scientists are looking for innovative methods of food production, which is a source of easily digestible protein with a balanced amino acid composition. Yeast protein biomass (single cell protein, SCP) is a bioavailable product which is obtained when primarily using as a culture medium inexpensive various waste substrates including agricultural and industrial wastes. With the growing population, yeast protein seems to be an attractive alternative to traditional protein sources such as plants and meat. Moreover, yeast protein biomass also contains trace minerals and vitamins including B-group. Thus, using yeast in the production of protein provides both valuable nutrients and enhances purification of wastes. In conclusion, nutritional yeast protein biomass may be the best option for human and animal nutrition with a low environmental footprint. The rapidly evolving SCP production technology and discoveries from the world of biotechnology can make a huge difference in the future for the key improvement of hunger problems and the possibility of improving world food security. On the market of growing demand for cheap and environmentally clean SCP protein with practically unlimited scale of production, it may soon become one of the ingredients of our food. The review article presents the possibilities of protein production by yeast groups with the use of various substrates as well as the safety of yeast protein used as food.